ETHICAL STANDARDS BETWEEN BUSINESS AND SOCIETAL ROLE OF MEDIA IN BOSNIA-HERZEGOVINA - Turčilo, Lejla; Buljubašić, Belma (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2017)
There is an extremely large number of media in Bosnia and Herzegovina, which at first glance gives the impression of pluralism and diversity of media content. However, since most media owners see the profit  as their own goal, ignoring the social role and responsibility of media, in the constant struggle to attract and keep public attention and to satisfy  advertisers' interests, the first thing that is in jeopardy are ethical standards. The social role of the media is placed in a subordinate position in relation to their business role. This paper presents the results of the research of attitudes of journalists and other actors of the media scene (analysts, NGOs, regulators, etc.) about media and non-media reasons for crisis of journalistic standards and ethics. The semi-structured interviews (with 44 respondents) were conducted in order to examine attitudes towards the quality of the media scene in BiH, and the key findings show that media neglect their societal role, since owners accept political and economic pressures, which causes censorship and self-censorship. Some of the possible solutions for such situation include: raising media literacy level, strengthening professional journalistic community and insisting on stronger respect of legal regulations and ethical standards.
Keywords: Bosnia and Herzegovina; Censorship; social responsibility; business; media; ethical standards